Spatiotemporal assessment and trend analysis of meteorological drought in Afghanistan (1974–2023) using SPI and SPEI indices - Abdur Rashid Jamalzi; Ghani Rahman; Fazlullah Akhtar; Qiyamud Din Ikram; Hyun-Han Kwon (Journal of Hydrology: Regional Studies)
Study region: Afghanistan, Central Asia. Study focus: Afghanistan has faced increasingly frequent and severe droughts since 1970s, affecting agriculture, and socio-economic stability. This study provides a spatiotemporal analysis of meteorological drought from 1974 to 2023 using the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI). Drought conditions were assessed at multiple timescales using high-resolution ERA5 reanalysis data. The Mann–Kendall test and Sen’s slope estimator identified trends, while correlation and regression analyses explored climatic drivers. New hydrological insights for the region: The analysis shows increasing drought duration, severity, and frequency, especially at longer timescales. Severe to extreme droughts occurred in 1985, 1999–2002, 2004, 2008, 2011, 2018, and 2021–2022. The Northern, Southern, Southwestern, and Western zones showed the strongest drying trends. A strong correlation between SPI and SPEI at the 12-month scale confirms their suitability for long-term monitoring. Drought in Afghanistan is primarily driven by precipitation, as confirmed by both indices. Additionally, temperature and evapotranspiration showed stronger negative correlations with SPEI, particularly in the southern and central zones, indicating their amplifying effect on drought severity in these regions. The study also shows a shift from seasonal to prolonged droughts, likely due to rising temperatures and shifting precipitation. These findings highlight the need for integrated drought early warning systems, adaptive water management, and climate-resilient agriculture to improve Afghanistan’s preparedness and resilience.